Hierarchical influence of enterprise departments on blockchain adoption: an analytic hierarchy process approach - Gharehdaghi, Mandana; Kamann, Dirk-Jan F. (Frontiers in Blockchain, 2025)
IntroductionThis study investigates how enterprise departments influence blockchain adoption.MethodsIt applies Isomorphism Theory and AHP using data from 156 professionals across 10 countries.ResultsFinance had the most influence, followed by Marketing, Production, HRM, and Purchasing.DiscussionInternal hierarchies and institutional pressures shape strategic adoption of blockchain.